Resilience in Online Learning: A Case Study for Language Learners - Fatin Nadifa Tarigan (Journal of English Education and Linguistics, 2021)
The Covid-19 pandemic has changed the world especially the education sector requiring the educators and students to carry out online/virtual home learning activities. The students with various assignments given by lecturers are required to be able to survive in difficult conditions started from must be able to survive in all pressures, tasks, and various problems experienced during online/virtual learning, must be able to demonstrate good academic resilience during the COVID-19 pandemic till must be able to survive in various conditions and in a state of covid-19. This study used descriptive qualitative research method with research subjects were the students in the English Education Study Program in Universitas Pembinaan Masyarakat Indonesia batch 2020/2021. The results showed that the academic resilience of students was in the high category with a percentage of 63% and in the medium category by 37%. It indicates that during the Covid-19 pandemic, students were able to survive in these conditions and were able to get out of the academic problems they experienced and were able to get out of the academic pressures that existed during the virtual or online teaching and learning process.